Examining correlates of feeding practices among parents of preschoolers. Issue 4 (December 2022) - Srivastava, Deepa; Zheng, Lucy R.; Dev, Dipti A.
Background: Parent feeding practices play a critical role in children's eating behaviors. Limited research has explored child-level correlates of parent feeding practices.Aim: To identify correlates of feeding practices (responsive and controlling) among parents of preschoolers US.Methods: Participants included parents (n = 273) of preschoolers (3–5 years), recruited from Early Care and Education settings (n = 24) located in a metropolitan city in the US. Analysis included descriptives, correlations, and multiple regression.Results: For responsive feeding practices, positive associations included child's weight with unintentional modeling ( β = .17, 95% CI [0.12, 0.53]), child vegetable consumption with behavioral role modeling ( β = 0.22, 95% CI [0.17, 0.44]), and parent monitoring with verbal modeling ( β = 0.21, 95% CI [0.12, 0.34]). For controlling feeding practices, parent restriction was positively associated with child weight concern ( β = 0.22, 95% CI [0.13, 0.39]) and parent monitoring ( β = 0.13, 95% CI [0.01, 0.19]), whereas child vegetable consumption was negatively associated ( β = −0.16, 95% CI [−0.27, −0.05]). Pressure to eat was negatively associated with child weight concern ( β = −0.18, 95% CI [−0.45, −0.09]), child fruit consumption ( β = −0.12, 95% CI [−0.37, −0.01]), household income ( β = −0.13, 95% CI [−0.30, −0.02]), and parent weight ( β = −0.14, 95% CI [−0.60, −0.05]), Conclusions: Findings highlight the importance of child characteristics when examining correlates of parent feeding practices, demonstrating bidirectional interactions between parent feeding practices and children's eating behaviors. Considering child-level correlates may improve the implementation of responsive feeding practices and reduce controlling feeding practices.